Effects of transmembrane pressure (TMP) on the performance of ultrafiltration (UF) membrane of soy protein - Ahmad Kamal, Hassan (2009)
The use of membrane separations using ultrafiltration (UF) in the fractionation of soy protein from soy milk has generated considerable interest, recently. Compared to traditional methods, UF gives higher yield and superior functional properties of the soy protein, and also allows the recovery of active soybean trypsin inhibitor (STI) for medical purposes. The performance of the UF membrane; in term of permeate flux, concentration of protein transmitted and retention ratio, by manipulating transmembrane pressure (TMP) to fractionate soy protein from soy milk is studied. Commercial soy milk samples have been centrifuged and introduced to the UF system at various TMP value. Data from the permeate flux, concentration of protein transmitted and retention ratio have been manipulated to get idea on the performance of the UF membrane. Based on the results, the range of effective TMP to fractionate soy protein from soy milk is between 15 to 20 psi. In this TMP range, the permeate flux is between 25 and 30 LMH, the concentration of protein transmitted is between 1.38 and 2.85 mg/mL and the retention ratio is 90%.